Expansion of tumor infiltrating lymphocytes (TIL) from bladder cancer. (2nd September 2018) - Poch, Michael; Hall, MacLean; Joerger, Autumn; Kodumudi, Krithika; Beatty, Matthew; Innamarato, Pasquale P.; Bunch, Brittany L.; Fishman, Mayer N.; Zhang, Jingsong; Sexton, Wade J.; Pow-Sang, Julio M.; Gilbert, Scott M.; et al.
ABSTRACT: Advanced bladder cancer patients have limited therapeutic options resulting in a median overall survival (OS) between 12 and 15 months. Adoptive cell therapy (ACT) using tumor infiltrating lymphocytes (TIL) has been used successfully in treating patients with metastatic melanoma, resulting in a median OS of 52 months. In this study, we investigated the feasibility of expanding TIL from the tumors of bladder cancer patients. Primary bladder tumors and lymph node (LN) metastases were collected. Tumor specimens were minced into fragments, placed in individual wells of a 24-well plate, and propagated in high dose IL-2 for four weeks. Expanded TIL were phenotyped by flow cytometry and anti-tumor reactivity was assessed after co-culture with autologous tumor digest and IFN-gamma ELISA. Of the 28 transitional cell bladder or LN tumors collected, 14/20 (70%) primary tumors and all of the LN metastases demonstrated TIL expansion. Expanded TIL were predominantly CD3 + (median 63%, range 10–87%) with a median of 30% CD8 + T cells (range 5–70%). TIL secreted IFN-gamma in response to autologous tumor. Addition of agonisitic 4-1BB antibody improved TIL expansion from primary bladder tumors regardless of pre-treatment with chemotherapy. This study establishes the practical first step towards an autologous TIL therapy process for therapeutic testing in patients with bladder cancer.